Macro-economic determinants of stock market co-movement beween China and United States. - Leng, Ruowei. (2011)
This study aims to examine the short run dynamics and long term relationships between the macro-economic fundamentals and the stock market returns of China and US, in the period 2000 to 2010. Prior research has largely laid emphasis on studying stock market interdependence of developed countries. In view of this, this study broadens our understanding by exploring the co-movement between US and the relatively young yet emerging economy of China. This paper employs well-accepted statistical methods such as the Augmented Dickey Fuller (ADF) test, Granger Causality, Johansen co-integration and Vector Error Correction Model (ECM). The results of the analysis revealed uni-directional and bidirectional causal relations among variables in the short run. Further, the ECM results revealed that the lags of China‟s interest rate and the stock returns are functions which have significant short-term effects on stock returns. While in the long run, the empirical results suggests that certain macro-economic fundamentals have a long run and contemporaneous effect on the stock market returns.